2009
DOI: 10.1007/s10562-009-9956-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound on the Structural and Textural Properties of Al–Fe Pillared Clays in a Concentrated Medium

Abstract: A modification of bentonite with the Al-Fe mixed system in a concentrated medium was performed, assisting the intercalation with ultrasound. The solid pillaring agent and clay powder were placed in a dialysis membrane in contact with a minimum amount of water, and ultrasound was used to promote species exchange. Al-Fe pillared clays (2, 5 and 10 mol% Fe) were characterized by XRF, CEC, XRD, H 2 -TPR and N 2 adsorption at 77 K, revealing changes in the structural and textural properties of the modified clays in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Although this method has had success in laboratory synthesis of pillared clays, it is not an ideal preparation technique for large scale production because large amounts of water and heat are necessary [14]. New procedures for the synthesis of pillared clays were proposed, using microwave irradiation or ultrasonic waves in order to decrease the consumption of three industrially-important parameters: time, water consumption and energy [15,16]. The high stability of the pillared clays prepared by ultrasonic was attributed to the uniform pillaring obtained by the use of ultrasonics, which did not alter properties such as acidity and catalytic activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although this method has had success in laboratory synthesis of pillared clays, it is not an ideal preparation technique for large scale production because large amounts of water and heat are necessary [14]. New procedures for the synthesis of pillared clays were proposed, using microwave irradiation or ultrasonic waves in order to decrease the consumption of three industrially-important parameters: time, water consumption and energy [15,16]. The high stability of the pillared clays prepared by ultrasonic was attributed to the uniform pillaring obtained by the use of ultrasonics, which did not alter properties such as acidity and catalytic activity [16].…”
Section: Introductionmentioning
confidence: 99%
“…This observation indicates that there is a beneficial effect of using ultrasound treatment and by adding the pillaring solution slowly to the clay suspension on amount of iron that incorporated into the structure. The use of ultrasound in the intercalation stage probably increases exchange of pillars and improves the dispersion and homogenization of the suspended solids [10]. Furthermore, from EDS analysis results, it was observed that, by changing the Fe/Fe + Cr ratio in the pillaring solution, the Fe/Cr ratio in pillared clay could be changed; the success of the replacement of iron and chromium in the structure was increased by pillaring with a solution containing an Fe/Fe + Cr ratio of 0.75.…”
Section: Analysis Of Sem-edsmentioning
confidence: 99%
“…For this reason, studies related to developing a more rapid synthesis of these materials have recently become important. At this point in the development of pillared clay catalysts for the industrial scale, it is important to improve their physicochemical and catalytic properties as well as to develop synthesis methods that decrease their production time and water use [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has become possible to decrease the volume of water by the use of concentrated suspensions, both clay and the pillaring agent [106][107][108][109][110][111]. Also, the time of intercalation of montmorillonite with chlorhydrol has been reduced through the use of ultrasound, having led to the obtaining of Al-PILC with a high thermal stability and textural properties superior to those of clay modified with an exchange time of 24 h. In overall, during the intercalation, treatment with ultrasound [51,112,113] and microwaves [107,[114][115][116] has been proved to be an adequate method for reducing the contact time between clay and the pillaring agent [57].…”
Section: Developments In the Synthesis Of Pillared Claysmentioning
confidence: 99%
“…Although, in the past 30 years, several studies highlighting some applications of industrial pillared clays have been published, such materials have not been used as commercial catalysts primarily due to the difficulty of extending the laboratory synthesis to an industrial scale [57]. However, in 2005, a procedure for pillaring clays with aluminum, which minimizes the processing time and the amount of water used, allowing its extension to an industrial level was developed.…”
Section: Developments In the Synthesis Of Pillared Claysmentioning
confidence: 99%